Incidence of Congenital Talipes Equinovarus among Children Reporting at Tertiary Care Hospital - Qurat-Ul-Ain, Saadia Muzadar, Kishwar Naheed, Aimen Malik, Muhammad Afzal, Farhan Riaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the incidence of congenital talipes equinovarus among children reporting at tertiary care hospital. Study setting & Duration: The study was conducted at Watim Medical & Dental College Rawat, Rawalpindi in the departments of Anatomy, Medical education & Dentistry from January 2021 to December 2021. Materials and Methods: There were 988 participants in this study. An easy questionnaire was used to gather information on children with CTEV who presented themselves to the outdoor department. Both consanguineous and non-consanguineous relationships were considered. Results: A total of 96 (9.7%) children presented with congenital talipes equinovarus or club foot and out of these children 56 (5.7%) patients were males and 40 (4.04%) were female. Conclusion: Clubfoot or congenital talipes equinovarus is one of the most common abnormalities of the foot and idiopathic talipes equinovarus is most common in the studied population. It is more common in males and is mostly bilateral. It should be detected at birth and treated early to prevent permanent disability.